DMGV Is a Rheostat of T Cell Survival and a Potential Therapeutic for Inflammatory Diseases and Cancers - Yang, Fengyuan Mandy; Shen, Liya; Fan, Dengxia Denise; Chen, Kuan-Hung; Lee, Jongdae (Frontiers in Immunology, 2022)
Activated effector T cells (Teff) and/or compromised regulatory T cells (Treg) underlie many chronic inflammatory diseases. We discovered a novel pathway to inhibit survival and expansion of Teff without compromising Treg survival and a potential therapeutic to treat these diseases. We found dimethylguanidino valeric acid (DMGV) as a rheostat for Teff survival: while cell-intrinsic DMGV generated by Alanine-Glyoxylate Aminotransferase 2 (AGXT2) is essential for survival and expansion by inducing mitochondrial ROS and regulation of glycolysis, an excessive (or exogenous) DMGV level inhibits effector T cell survival, thereby the AGXT2-DMGV-ROS axis functioning as a switch to turn on and off Teff expansion. DMGV-induced ROS is essential for glycolysis in T cells, and paradoxically DMGV induces ROS only when glycolysis is active. Mechanistically, DMGV rapidly activates mitochondrial calcium uniporter (MCU), causing a surge in mitochondrial Ca2+ without provoking calcium influx to the cytosol. The mitochondrial Ca2+ surge in turn triggers the mitochondrial Na+/Ca2+ exchanger (NCLX) and the subsequent mitochondrial Na+ import induces ROS by uncoupling the Coenzyme Q cycle in Complex III of the electron transport chain. In preclinical studies, DMGV administration significantly diminished the number of inflammatory T cells, effectively suppressing chronic inflammation in mouse models of colitis and rheumatoid arthritis. DMGV also suppressed expansion of cancer cells in vitro and in a mouse T cell leukemic model by the same mechanism. Our data provide a new pathway regulating T cell survival and a novel mode to treat autoimmune diseases and cancers.